Improving of Surface Quality of Metal Reflector Mirrors Machined by Single Point Diamond Turning - G. A. Gusakov; G. V. Sharonov (Приборы и методы измерений)
Improving the technology of diamond turning of aluminum alloys is of great importance for expanding the application areas of metal-optical products based on aluminum in aerospace technology. The aim of this work was to study the effect of surface inhomogeneities of the initial aluminum alloy substrates on their optical and mechanical characteristics and to determine ways of improving the quality of aluminum reflector mirrors manufactured using nanoscale single point diamond turning. The investigated reflector mirrors were made from AMg2 aluminum alloy. The optical surface treatment was carried out on a precision turning lathe with an air bearing spindle using a special diamond cutter with a blade radius of ≤ 0.05 μm. The analysis of the surface structure of the AMg2 alloy substrates was carried out by scanning electron microscopy / electron microprobe. The quality control of the surface treatment of the manufactured reflector mirrors was carried out by atomic force microscopy. The reflectivity and radiation resistance of these samples were also investigated.It is shown that an important problem in the manufacture of optical elements from aluminum alloys is the inhomogeneity of the structure of the initial material, associated with the presence of intermetallic inclusions. Heat treatment of the AMg2 alloy substrates at T ≥ 380 °C makes it possible to improve the quality of surface and the radiation resistance of aluminum mirrors both by removing mechanical stresses and by partially homogenizing the starting material. The optimum is heat treatment at the maximum allowable temperature for the AMg2 alloy T = 540 ºС, as a result of which there is a complete disappearance of intermetallic inclusions with an increased magnesium content. The use of high-temperature heat treatment of AMg2 alloy substrates allows, in comparison with unannealed samples, to reduce the surface roughness from 1.5 to 0.55 nm, to increase the reflectivity of mirrors at a wavelength of 1064 nm from 0.89 to 0.92, and to increase the laser damage threshold from 3.5 to 5 J / cm2.